2021
DOI: 10.3390/v13081671
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Zika Infection and the Risk of Neurodevelopmental, Neurological, and Urinary Track Disorders in Early Childhood. A Systematic Review

Abstract: It was late 2015 when Northeast Brazil noticed a worrying increase in neonates born with microcephaly and other congenital malformations. These abnormalities, characterized by an abnormally small head and often neurological impairment and later termed Congenital Zika Syndrome, describe the severity of neurodevelopmental and nephrological outcomes in early childhood, and the implication of microcephaly at birth. The purpose of the study was to describe the neurodevelopmental outcomes in children exposed to Zika… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
(70 reference statements)
1
5
0
Order By: Relevance
“…8 Two recently published systematic reviews confirmed the importance of continuous monitoring of these children and their growth to better understand and control postnatal complications. 9,10 Recognising that ZIKV affects many structures of the central nervous system, including those that control physiological functioning of the bladder and urinary sphincter, supports the hypothesis that intrauterine ZIKV infection can affect urinary function. [11][12][13][14] A study conducted in Rio de Janeiro, including children with confirmed CZS, was the first to describe a urodynamic pattern suggestive of neurological lower urinary tract dysfunction (NLUTD), with reduced bladder capacity and higher vesical pressure during bladder filling in this population.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…8 Two recently published systematic reviews confirmed the importance of continuous monitoring of these children and their growth to better understand and control postnatal complications. 9,10 Recognising that ZIKV affects many structures of the central nervous system, including those that control physiological functioning of the bladder and urinary sphincter, supports the hypothesis that intrauterine ZIKV infection can affect urinary function. [11][12][13][14] A study conducted in Rio de Janeiro, including children with confirmed CZS, was the first to describe a urodynamic pattern suggestive of neurological lower urinary tract dysfunction (NLUTD), with reduced bladder capacity and higher vesical pressure during bladder filling in this population.…”
Section: Introductionmentioning
confidence: 96%
“…Currently, 7 years after its first publication, much has been discussed about brain patterns, 2 neurological conditions, 6 growth, 7 and motor, cognitive, and sensory impairment 8 . Two recently published systematic reviews confirmed the importance of continuous monitoring of these children and their growth to better understand and control postnatal complications 9, 10 …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, SCZ is a new syndrome, so its characterization is important and for which neurodevelopmental assessments are a valuable tool. In previous reports of infants exposed to ZIKV during pregnancy, it was observed that the risk of developing neurodevelopmental disorders may be related to the presence of microcephaly [ 22 , 47 ]. The risk of neurodevelopmental delay can range from 13.8% to 20.2% in normocephalic infants, while this percentage increases from 99.1% to 100% when infants develop severe microcephaly or from 65% to 70% in cases of moderate microcephaly [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The high incidence of cases in pregnant women is important due to the fact that ZIKV infection during pregnancy has been associated with the development of anomalies in newborns [ 11 ], such as morphological–cranial [ 12 ], cerebral [ 13 , 14 , 15 ], ophthalmic [ 16 ], neurological [ 17 ], and joint contractures [ 18 , 19 ], which have been grouped into a new syndrome called Congenital Zika Syndrome (CZS) [ 11 , 20 ]. Some anomalies caused by intrauterine ZIKV infection can manifest postnatally, such as postnatal microcephaly [ 21 ] and neurodevelopmental disorders, that could affect cognitive, motor, and social functions [ 22 ], even in healthy infants [ 23 ]. Neurodevelopmental assessment in infants exposed to ZIKV during pregnancy is of great importance because it allows the characterization of the effects of gestational ZIKV infection at birth and in the long term, due to the possible impairment of cognitive, motor, and social skills in infants.…”
Section: Introductionmentioning
confidence: 99%
“…These findings were characterized as Neurogenic Bladder (NB) with risk for the upper urinary tract. In a recent systematic review, the first studies addressing to LUT function presented discordant findings and methodological criticisms [ 19 ].…”
Section: Introductionmentioning
confidence: 99%